A PORTRAIT OF EFL LEARNERS’ DIFFICULTIES AND STRATEGIES IN ANSWERING LISTENING COMPREHENSION OF TOEFL ITP PREDICTION TEST AT ONLINE ENGLISH COURSE - Nisa Alzana (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study aimed to discover the most common difficulties of listening comprehension for TOEFL ITP prediction test as well as the learners’ strategies to overcome their difficulties. This study employed descriptive quantitative method with purposive sampling technique. There were 30 participants were found significantly from Indonesian EFL learners at online English course and 5 out of 30 students who were interviewed. The procedure of the research involved two steps; administering a questionnaire and conducting an interview. The finding of this study showed that the most common EFL learners’ difficulties in answering listening comprehension of TOEFL ITP prediction test are the choice of words and foreign terms (M = 4.73), followed by the speaker’s speed (M = 4.60), speaker’s accent (M = 4.50), speaker’s intonation (M = 4.37), and speaker’s length of talk (M = 4.30). The learners employed various strategies to overcome each difficulty such as practicing frequently in various learning sources, anticipating the questions, drawing the speaker’s conclusion and details of the topic in answering the test, and becoming familiar with American accent by watching YouTube videos, movies, and listening to English songs.Keywords: Listening Comprehension, TOEFL ITP, Prediction Test